Pore Structural Features of Granite under Different Temperatures - Hongmei Gao (MDPI AG, 2021)
To explore the effects of thermal actions on the pore structural features of granite, scanning electron microscope (SEM) and mercury injection experiments were carried out on granite after thermal treatment (25 °C to 400 °C). The pore structure was investigated from various perspectives, including the capillary pressure curve, the pore–throat ratio, the median saturation pressure, the median pore–throat radius, the porosity, the pore volume, and the pore size distribution. Based on mercury intrusion test data, the Winland model of permeability prediction was modified for a high-temperature tight granite reservoir. The results showed that: (1) As the temperature rose, the mercury injection curve was gradually flattened, and the mercury ejection efficiency gradually increased. Meanwhile, the pore–throat ratio and the median saturation pressure decreased exponentially, and the pore connectivity was enhanced. (2) The median pore–throat radius and the porosity of granite increased exponentially as the temperature increased. Above 200 °C, the median pore–throat radius and the porosity increased substantially. (3) The pore volumes of the transitional pores, mesopores and macropores, and the total pore volume inside the granite, increased as the temperature rose. Especially above 200 °C, the transitional pores and the mesopores were prominently developed, and the pore volumes of the transitional pores and the mesopores took up a significantly greater proportion of the total pore volume. (4) As the temperature rose, the pore size distribution of granite became more extensive, the pore–throat structure was obviously developed, and the pore–throat connectivity was enhanced. (5) The relationship between the micropores’ characteristic parameters and the macro-permeability in engineering was established though a modified Winland model, and the modified Winland model had a better prediction effect. The findings provide a solid basis for rock geothermal mining projects and related geotechnical engineering.